Antibacterial polylactic acid/chitosan nanofibers decorated with bioactive glass - Goh, Y. F. (Elsevier B.V., 2016)
In this study, we have presented the structural and in vitro characterization of electrospun polylactic acid (PLA)/Chitosan nanofibers coated with cerium, copper or silver doped bioactive glasses (CeBG/CuBG/AgBG). Bead-free, smooth surfaced nanofibers were successfully prepared by using electrospinning technique. The nanocomposite fibers were obtained using a facile dip-coating method, their antibacterial activities against E. coliE. coli (ATCC 25922 strains) were measured by the disk diffusion method after 24 h of incubation at 37 °C. CeBG and CuBG decorated PLA/Chitosan nanofibers did not develop an inhibition zone against the bacteria. On the other hand, nanofibers coated with AgBG developed an inhibition zone against the bacteria. The as-prepared nanocomposite fibers were immersed in SBF for 1, 3 and 7 days in Simulated Body Fluid (SBF) for evaluation of in vitro bioactivity. All samples induced the formation of crystallites with roughly ruffled morphology and the pores of fibers were covered with the extensive growth of crystallites. Energy Dispersive X-ray (EDX) composition analysis showed that the crystallites possessed Ca/P ratio close to 1.67, confirming the good in-vitro bioactivity of the fibers.